(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate in vitro the roughness and surface morphology of composite resins (CRs) stored for 180 days in acidic solutions present in the diet. Three micro-hybrid composite resins were used in this study (Charisma, Opallis, and Esthet-X). Fifty-one specimens were made of each material with 4 mm in diameter and 2 mm thick with the aid of an elastomer matrix. After photoactivation for 40 seconds (Elipar Free-Light / 3M ESPE), the specimens were stored in distilled water for 24 hours at 37ºC for subsequent surface polishing with Soft Lex / 3M ESPE discs in fine and extra-fine granulation. Then, the specimens were dried with absorbent paper and the surface roughness was measured using a rugosimeter. The specimens were then randomly divided into five groups (n=10) according to the tested solutions: DW - Distilled water (pH 5.30); RW - Red Wine / Trapiche Syha Ind. Argentina red wine (pH 3.68); CK – Coke / Coca Cola Co. (pH 2.73), OJ - Orange juice / Purity Cocamar (pH 3.58) and LBS - lactate buffer solution (pH 2.74). The tested solutions were changed daily. The surface roughness test was repeated after 15, 90 and 180 days of immersion. The average values of surface roughness were submitted to LSmeans analysis and Tukey-Kramer test, at a significance level of 5%. The results of surface roughness revealed that all CRs showed a significant increase in the roughness values over time for all tested solutions.